(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The crude methanol extracts of the leaf of Lophopetalum fimbriatum (non Wight) F. Vill. and Calophyllum inophyllum L. as well as their pet-ether, carbon tetrachloride, chloroform and aqueous soluble fractions were evaluated for antioxidant, cytotoxic, thrombolytic, membrane stabilizing and antimicrobial activities. The antioxidant potential was evaluated by DPPH and Folin-Ciocalteau reagent using butylated hydroxytolune (BHT) and ascorbic acid as standards, respectively. Among the extractives of L. fimbriatum and C. inophyllum, the chloroform soluble fraction and methanolic crude extract demonstrated the highest free radical scavenging activity (IC50 = 175.57 ± 0.02 ?g/ml and IC50 = 1.0 ± 0.22 ?g/ml) which could be correlated with their total phenol contents 82.15 ± 0.89 and 32.19 ± 0.81 mg of GAE /g of extractives, respectively. In the brine shrimp lethality bioassay, the carbon tetrachloride soluble fractions of L. fimbriatum (LC50 = 0.515 ± 0.03 ?g/ml) and C. inophyllum (LC50 = 0.77 ± 0.18 ?g/ml) revealed general toxicity. During assay for thrombolytic activity, the carbon tetrachloride soluble materials of L. fimbriatum and the chloroform soluble fraction of leaf of C. inophyllum revealed clot lysis by 8.89 ± 1.410% and 27.84 ± 0.94%, while the standard streptokinase and water, used as positive and negative controls, demonstrated 66.77% and 3.79% clot lysis, respectively. In hypotonic solution and heat induced conditions, the crude methanol extracts of L. fimbriatum and C. inophyllum inhibited haemolysis of human erythrocyte by 68.14 ± 2.05% & 40.00 ± 1.6% and 57.67 ± 0.26% and 28.12 ± 0.38%, respectively. Here, acetyl salicylic acid (0.1 mg/ml) was used as reference showing 72.79% and 42.12% haemolysis of RBCs in hypotonic solution and heat induced conditions, respectively. The antimicrobial activity was assessed by the disc diffusion method and the chloroform soluble fraction of L. fimbriatum demonstrated 16.0 mm zone of inhibition against Sarcina lutea. Different extractives of C. inophyllum inhibited microbial growth with zone of inhibition ranging from 10.0 mm to 22.0 mm. Among the different extractives of C. inophyllum, the pet-ether and carbon tetrarchloride soluble fractions demonstrated 22.0 mm zone of inhibition against Vibrio parahaemolyticus and Pseudomonas aeruginosa, respectively. DOI: http://dx.doi.org/10.3329/bpj.v16i2.22305 Bangladesh Pharmaceutical Journal 16(2): 205-209, 2013